2009
DOI: 10.1002/nbm.1360
|View full text |Cite
|
Sign up to set email alerts
|

Proton spectroscopic imaging of the human prostate at 7 T

Abstract: The sensitivity of proton MR Spectroscopic Imaging ((1)H-MRSI) of the prostate can be optimized by using the high magnetic field strength of 7 T in combination with an endorectal coil. In the work described in this paper we introduce an endorectal transceiver at 7 T, validate its safety for in vivo use and apply a pulse sequence, optimized for three-dimensional (3D) (1)H-MRSI of the human prostate at 7 T. A transmit/receive endorectal RF coil was adapted from a commercially available 3 T endorectal receive-onl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
68
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(69 citation statements)
references
References 28 publications
0
68
1
Order By: Relevance
“…However, spectroscopic images could be made with the endorectal transceiver using a semi-LASER sequence with MEGA [Mescher Garwood (named after the authors)] water and lipid suppression with FOV ¼ 50 Â 40 Â 50 mm 3 , acquisition matrix of 7 Â 7 Â 8 and TR/TE ¼ 1.6/56 ms (5). Clear resonances of choline, creatine and citrate can be seen (Fig.…”
Section: In Vivo Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, spectroscopic images could be made with the endorectal transceiver using a semi-LASER sequence with MEGA [Mescher Garwood (named after the authors)] water and lipid suppression with FOV ¼ 50 Â 40 Â 50 mm 3 , acquisition matrix of 7 Â 7 Â 8 and TR/TE ¼ 1.6/56 ms (5). Clear resonances of choline, creatine and citrate can be seen (Fig.…”
Section: In Vivo Measurementsmentioning
confidence: 99%
“…For spectroscopic imaging of the prostate with the eight-element microstrip array, conventional pulses are not suitable, as these pulses cannot obtain a sufficiently high amplitude within the available power and SAR limitations to achieve sufficient bandwidth. Adiabatic sliceselective refocusing pulses that have a much larger bandwidth were therefore considered for volume-selective spin manipulation, similar to Klomp et al (5).…”
Section: In Vivo Measurementsmentioning
confidence: 99%
“…Klomp et al demonstrated the successful detection of resonances of spins of potential tumor markers like creatine and choline [63]. They applied an endorectal transceiver coil system and a pulse sequence with slice selective adiabatic refocusing pulses [63].…”
mentioning
confidence: 99%
“…Klomp et al demonstrated the successful detection of resonances of spins of potential tumor markers like creatine and choline [63]. They applied an endorectal transceiver coil system and a pulse sequence with slice selective adiabatic refocusing pulses [63]. Recent publications have mainly focused on the optimization of coil systems for ultra-high-field prostate imaging, as deeply localized organs are known to be challenging with respect to spin excitation and signal reception [64,65].…”
mentioning
confidence: 99%
“…For mpMRI, full 3D acquisition is usually most appropriate. For coupled spin systems, it is essential to select the acquisition echo time to achieve the optimal in-phase signals (eg, for lactate 27 and citrate in prostate 28 ). The repetition time should be chosen with reference to expected metabolite T 1 to achieve optimal SNR per unit time.…”
Section: Technical Challenges In Data Acquisitionmentioning
confidence: 99%